Communication, cultural and media studies - Hartley, John, 1948- (2020)
"Now in its fifth edition, this pioneering volume of Routledge's 'Key Concepts' series offers clear explanations of key concepts, showing where they came from, what they are used for, and why they provoke discussion or disagreement. The new edition is extensively revised to keep pace with rapidly evolving developments in communication, culture and media, providing topical and authoritative guidance to transformational shifts from broadcast to digital technologies, national to global media and disciplinary to diverse knowledge"--
Includes bibliographical references and index.
Keywords: Communication; Mass media; Communication and culture